PERAN SEKOLAH DALAM PEMEROLEHAN BAHASA ANAK USIA 7 TAHUN DI SDN 185 INPRES SALOMATTI - Dania Gaffar; Mahfuddin; Aryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the forms of vocabulary and sentence patterns used by 7-year-old children and to examine the role of the school in supporting children’s language acquisition at SDN 185 Inpres Salomatti. This research employed a qualitative approach with a descriptive method. The participants consisted of 7-year-old students and classroom teachers at SDN 185 Inpres Salomatti. Data were collected through observation, interviews, documentation, and recordings of children’s utterances during school activities. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that the language acquisition of 7-year-old children develops dynamically and contextually. In terms of vocabulary, children use words from Indonesian, daily language, regional dialects, and mixed-language expressions influenced by social interactions and digital media. Regarding sentence patterns, children are able to construct simple and complex sentences, although some utterances do not fully conform to standard grammatical rules. They also demonstrate the ability to use declarative, interrogative, and imperative sentences according to communicative needs. Furthermore, the school plays a significant role in language development, with teachers serving as language models and peers acting as communication partners. Therefore, the school functions as a supportive social and academic environment for children’s language development through meaningful and communicative interactions.